IMPLEMENTASI KEBIJAKAN INTEGRASI APLIKASI PENGELOLAAN KEUANGAN DAERAH DALAM MENINGKATKAN KUALITAS LAYANAN KEUANGAN DI KABUPATEN KOTAWARINGIN BARAT - Rochim Hidayat; R. Biroum B; Holten Sion (Halu Oleo University, 2025)
This study aims to analyse and describe the implementation of the financial application integration policy in Kotawaringin Barat Regency, as well as to identify the supporting and inhibiting factors influencing its implementation. Data analysis was conducted using an interactive analysis technique, which includes data collection, data reduction, data presentation, and conclusion drawing. The findings of this study indicate that the implementation of the financial application integration policy in Kotawaringin Barat Regency is as follows: (1) The policy implementation, particularly in regional financial management, has been running optimally. (2) Several internal and external factors contribute to the effectiveness of policy implementation, including: 1) Leadership support and regulatory framework; 2) Availability of resources; 3) Infrastructure support; 4) Organisational work culture; 5) Technical assistance; and 6) Coordination and networking between institutions. (3) The identified inhibiting factors include: 1) Technical limitations of the application; 2) Lack of continuous technical support; 3) Inconsistent policy support; 4) Limited system integration; and 5) System complexity.